Isothiocyanates and Xenobiotic Detoxification. Issue 18 (12th February 2018) - Abdull Razis, Ahmad Faizal; Konsue, Nattaya; Ioannides, Costas
Abstract: The potential of isothiocyanates to antagonize the carcinogenicity of structurally diverse chemicals has been established in animals. A feasible mechanism of action involves protecting DNA by reducing the availability of the genotoxic metabolites of chemical carcinogens by either inhibiting their generation and/or stimulating their detoxification. In vivo as well as in vitro studies conducted in rat/human primary hepatocytes and precision‐cut tissue slices have revealed that isothiocyanates can impair cytochrome P450 activity, including the CYP1 family which is the most active in the bioactivation of carcinogens, by virtue of being mechanism‐based inactivators. The aromatic phenethyl isothiocyanate is the most effective of those studied, whereas aliphatic isothiocyanates such as sulforaphane and erucin necessitate high doses in order to manifest such effects that may not always be achievable through the diet. In all systems studied, isothiocyanates are strong inducers of detoxification enzyme systems including quinone reductase, glutathione S ‐transferase, epoxide hydrolase, and UDP‐glucuronosyl transferase. Indeed, in smokers phenethyl isothiocyanate intake increases the urinary excretion of inactive mercapturate metabolites of toxic chemicals present in tobacco. Glucosinolates, the precursors of isothiocyanates, have also the potential to upregulate detoxification enzyme systems, but their contribution to the cancer chemoprevention linked to cruciferous vegetable consumption remains to be evaluated. Abstract : Isothiocyanates are a class of chemicals present in many widely consumed vegetables such as broccoli and radishes. Their consumption has been demonstrated in many studies to decrease the risk of cancer. One of their major mechanisms of action is to enable the body to tackle cancer‐causing chemicals to which humans are invariably and inevitably exposed. They enable the body to eliminate them before they have a chance to damage DNA that may lead to cancer.